The Multimodal MOPr/DOPr Agonist LP2 Reduces Allodynia in Chronic Constriction Injured Rats by Rescue of TGF-β1 Signalling - Fidilio, Annamaria; Grasso, Margherita; Turnaturi, Rita; Caruso, Giuseppe; Spitale, Federica Maria; Vicario, Nunzio; Parenti, Rosalba; Spoto, Salvatore; Musso, Nicolò; Marrazzo, Agostino; Chiechio, Santina; Caraci, Filippo; et al. (Frontiers in Pharmacology, 2021)
Neuropathic pain is one of the most disabling forms of chronic pain and it is characterized by hyperalgesia and allodynia linked to an aberrant processing of pain transmission and to neuroinflammation. Transforming growth factor-β1 (TGF-β1) is an anti-inflammatory cytokine, which protects against neuroinflammation. It has been demonstrated that TGF-β1 and opioid receptors signalling crosstalk results in an improvement of endogenous opioid analgesia, but it is not known whether mu opioid peptide receptor (MOPr) or delta opioid peptide receptor (DOPr) agonists can positively modulate TGF-β1 pathway. In the present study, we examined the correlation between anti-allodynic effect of LP2, a dual-target MOPr/DOPr agonist, and TGF-β1 signalling in the chronic constriction injury (CCI) model. We detected a significant decrease of active TGF-β1 and of its type II receptor TGFβ-R2 levels in the spinal cord from CCI rats and a selective deficit of TGF-β1 in microglia cells both at days 11 and 21 post-ligature, as assessed by immunofluorescence analysis. LP2, when administered from the 11 days post-ligature to 21 days, was able to reduce CCI-induced mechanical allodynia by rescue of TGF-β1 and TGFβ-R2 levels. Our data suggest that the rescue of TGF-β1 signalling by dual-target MOPr/DOPr agonist LP2 could be mediated by DOPr activation in spinal microglia, thus the dual-target approach could represent a novel pharmacological approach to increase the analgesic efficacy of MOPr agonists.